أسباب الحظر في الأطعمة الحيوانية: دراسة تأصيلية فقهية من منظور الفقه المالكي ........................... Causes of Prohibition in Animal Food: Legal Inquiry from Maliki Perspective - ياحي, مصطفى (الدراسات الإسلامية, 2018)
This paper investigates the causes of prohibition in animal food upheld in the Maliki School. The writer, after providing a linguistic and technical explanation of the terms employed in this regard, proceeds to identify eight causes of prohibition that have been recognized in this school. According to the writer’s finding, most of these causes are common in other schools as well except prohibition due to hygienic considerations. The latter is specific to Maliki School. The writer has concluded that the Maliki School maintains a broader outlook toward prohibition of animal food in comparisons to other schools of Islamic Law.